2020
DOI: 10.1186/s12879-020-4840-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of healthcare-associated infection in elderly patients in a large Chinese tertiary hospital: a 3-year surveillance study

Abstract: Background: We analyzed the results of a 3-year surveillance study on the epidemiological and clinical characteristics of healthcare associated-infections (HAIs) in elderly inpatients in a large tertiary hospital in China. Methods: Real-time surveillance was performed from January 1, 2015 to December 31, 2017. All HAIs were identified by infection control practitioners and doctors. Inpatient data were collected with an automatic surveillance system.Results: A total of 134,637 inpatients including 60,332 (44.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
2
11
1
Order By: Relevance
“… 21 According to a three-year surveillance study of 134,637 patients, urinary tract infections are the second most common healthcare-associated infections among the elderly, and catheter-associated urinary tract infections are more prevalent among the needy. 22 In the present study, a significant reduction in the incidence of POUR after TEAS treatment was observed as compared to the baseline incidence of 15% in the elderly, which was consistent with previous research. Furthermore, no urinary tract infections occurred in patients treated with TEAS, indicating that TEAS has a protective effect on urinary tract susceptibility in older adults.…”
Section: Discussionsupporting
confidence: 93%
“… 21 According to a three-year surveillance study of 134,637 patients, urinary tract infections are the second most common healthcare-associated infections among the elderly, and catheter-associated urinary tract infections are more prevalent among the needy. 22 In the present study, a significant reduction in the incidence of POUR after TEAS treatment was observed as compared to the baseline incidence of 15% in the elderly, which was consistent with previous research. Furthermore, no urinary tract infections occurred in patients treated with TEAS, indicating that TEAS has a protective effect on urinary tract susceptibility in older adults.…”
Section: Discussionsupporting
confidence: 93%
“…With an increasing number of studies in this field demonstrating the accuracy and efficiency of RT-NISS on HAI surveillance, health care authorities increasingly demand the installation and daily use of RT-NISSs as a part of quality management. Our data showed that RT-NISS could adequately and accurately collect HAI cases, which is in agreement with other studies [ 12 , 16 , 22 ]. Furthermore, RT-NISS improves the accuracy of MDRO infection case reports, and the adoption of a RT-NISS coupled with intervention implementations can reduce the infection incidences of HAIs and MDROs.…”
Section: Discussionsupporting
confidence: 93%
“…Although the proportion of fungi in gut microbiota is low, it is closely associated with the feeding, immunity, and metabolic health of the host (6)(7)(8). Studies on the relationship between gut fungi and host health have confirmed that an imbalance in the gut fungal flora can cause diarrhea (9,10). The intestinal abundance of Neocallimastigomycota in diarrhea yaks was found to be significantly higher than that of healthy yaks, suggesting that Neocallimastigomycota may be associated with diarrhea (11).…”
Section: Introductionmentioning
confidence: 99%